DETERMINAN FAKTOR YANG MEMPENGARUHI PROFITABILITAS BANK DIGITAL YANG TERDAFTAR DI BEI - Putra, Moh. Rizqy Eka; Pasaribu, Gymnastiar Eka Aurillina; Fisabilillah, Ladi Wajuba Perdini; Ma'ruf, Aminudin (Jurnal Ekonomika : INDEPENDEN, 2025)
This research aims to analyze the determinants of factors that influence the profitability of digital banks listed on the Indonesia Stock Exchange (BEI) during the 2018–2023 period. The independent variables tested include Non-Performing Loans (NPL), Capital Adequacy Ratio (CAR), and Operational Costs to Operating Income (BOPO), with Return on Assets (ROA) as the dependent variable. The method used is quantitative with panel data regression using Eviews 10 software. The research sample consists of six digital banks that meet the criteria, with a total of 30 observations. The research results show that NPL has a positive but not significant effect on ROA, CAR has a positive and significant effect on ROA, while BOPO has a significant negative effect on ROA. These findings indicate that operational efficiency and capital adequacy are key factors in increasing digital bank profitability. Therefore, digital banks need to improve operational efficiency and maintain a strong capital position to maintain optimal financial performance.